The Relationship Of Environmental Sanitation With The Event Of Diarrhea On Children In The Working Area Of The Sihepeng Health Center - Reni Agustina Harahap; Widia Alwiyah (International Archives of Medical Sciences and Public Health, 2022)
Background: Based on data from the Central Statistics Agency (BPS) of North Sumatra in 2019 it was stated that the main water sources most used by households for drinking were pump water (21.44%), tap water (11.84%) and protected wells ( 11. 27%) and according to data from Riskesdas in 2013 it is known that 65.2% of households in Indonesia use healthy latrines. Objective: This study aims to determine the relationship between environmental sanitation and the incidence of diarrhea in children under five in the working area of ??the Sihepeng Public Health Center. Methods: This type of research uses quantitative research with a case control approach which was conducted from August 2021 to February 2022 in the working area of ??the Sihepeng Health Center, Mandailing Natal Regency. The sample in this study were 42 respondents with diarrhea and 42 respondents without diarrhea with a total sample of 84 respondents. The analysis was carried out by univariate analysis and bivariate analysis by Chi-Square test. Research Results: Based on the results of bivariate analysis, latrine ownership was obtained (p=0.046), drinking water source (0.023), and physical quality of clean water (p=0.395). Conclusion: The analysis proves that there is a significant relationship between ownership of latrines and drinking water sources with the incidence of diarrhea in children under five in the work area of ??the Sihepeng Public Health Center.